The Complete Peanuts, 1977 to 1978 - Schulz, Charles M. (Charles Monroe), 1922-2000 (Fantagraphics Books, 2010)
Collects all the "Peanuts" comic strips published from 1977 to 1978 in newspapers, including both daily and Sunday strips.